Eksistensi Gerakan Muhammadiyah dalam Pendidikan di Era Modernisasi (Studi Kasus MI Muhammadiyah Pallatabbua, MTs Muhammadiyah Mandalle, MA Muhammadiyah Limbung) - Lukman Ismail; Risfaisal Risfaisal (Equilibrium: Jurnal Pendidikan, 2017)
Abstract. The main problem in this research is Muhammadiyah in education. The purpose of this research is (i) To know the implementation of the Muhammadiyah movement in education in the era of modernization. (ii) To know the dynamics of the Muhammadiyah movement in education in the era of modernization. The type of research conducted is descriptive qualitative research aimed at understanding social reality. The informant is determined by purposive sampling, based on the characteristic of the informant that has been determined. The results of this study indicate that (i) the implementation of the Muhammadiyah movement is PK TM I and PK TM 2 which aim to have students siddiq, tabligh, amanah, fathonah and Hisbul Wathan (HW) activities to prepare and nurture children, adolescents and youth so have aqidah, mental and physical, knowledgeable and technologically and morals karimah. (ii) the dynamics of the Muhammadiyah movement: the issuance of the Letter of the 3 Ministers which made Madrasah education strong enough to be in line with the public schools, the decentralization of education which gave full rights to the regions, the application of ISMUBA (Al-Islam, Kemuhammadiyahan, Arabic) curriculum and the development of student character, teachers and employees in the ISMUBA.Keywords: Existence, Muhammadiyah Movement, Education.